2022
DOI: 10.3390/cells11244095
|View full text |Cite
|
Sign up to set email alerts
|

TRIP13 Participates in Immediate-Early Sensing of DNA Strand Breaks and ATM Signaling Amplification through MRE11

Abstract: Thyroid hormone receptor-interacting protein 13 (TRIP13) participates in various regulatory steps related to the cell cycle, such as the mitotic spindle assembly checkpoint and meiotic recombination, possibly by interacting with members of the HORMA domain protein family. Recently, it was reported that TRIP13 could regulate the choice of the DNA repair pathway, i.e., homologous recombination (HR) or nonhomologous end-joining (NHEJ). However, TRIP13 is recruited to DNA damage sites within a few seconds after da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…5A). To determine if any of these genes may play a role in PTCL maintenance, we utilized data from CRISPR knockout screens in the DepMap database (Broad Institute, (39,40)) and investigated whether any of the genes affected the growth of hematologic cell lines. This search revealed that knockouts of most genes did not signi cantly impact the proliferation of hematological cell lines, as indicated by the gene effect scores ranging from − 0.75 to + 0.75 (Figs.…”
Section: Loss Of Dna Methylation Correlates With Up-regulation Of Gen...mentioning
confidence: 99%
See 1 more Smart Citation
“…5A). To determine if any of these genes may play a role in PTCL maintenance, we utilized data from CRISPR knockout screens in the DepMap database (Broad Institute, (39,40)) and investigated whether any of the genes affected the growth of hematologic cell lines. This search revealed that knockouts of most genes did not signi cantly impact the proliferation of hematological cell lines, as indicated by the gene effect scores ranging from − 0.75 to + 0.75 (Figs.…”
Section: Loss Of Dna Methylation Correlates With Up-regulation Of Gen...mentioning
confidence: 99%
“…The AAA ATPase TRIP13 (thyroid hormone receptor interactor 13) is known to participate in various regulatory steps related to the cell cycle, such as the mitotic spindle assembly checkpoint and meiotic recombination, as well as the DNA repair by immediate-early DNA damage sensing and ATM signaling activation 39 . To determine if TRIP13 is required for the proliferation of PTCL, we transduced a PTCL-NOS cell line, T8ML-1, with lentiviruses expressing shRNAs either targeting scrambled or TRIP13 and coexpressing mCherry.…”
Section: Trip13 Downregulation Inhibits the Proliferation Of Malignan...mentioning
confidence: 99%
“…Thyroid hormone receptor interactor 13 (TRIP13) is a member of the AAA+ ATPase family able to generate mechanical stresses through ATP hydrolase activities ( 1 ). TRIP13 was initially identified as a protein that interacts with the E1 protein of the human papillomavirus ( 2 ).…”
Section: Introductionmentioning
confidence: 99%